CETP Pharmacological Manipulation Transforming Human into Mouse: Is this Still a Viable Hypothesis? - Morales-Villegas, Enrique; Moreno-Virgen, Gualberto; J. Barter, Philip (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2012)
Manipulating the action of the Cholesteryl Ester Transfer Protein -CETP- and transforming the human lipid phenotype into one resembling the mouse lipid phenotype, in order to reduce susceptibility to atherosclerosis, is a hypothesis based on at least three lines of scientific evidence summarized within the introduction of this article. The following aspects related to the pharmacological manipulation of the CETP are discussed within the present article: a) CETP as a controversial protein involved in heterotypic and homotypic transport of neutral lipids between different lipoproteins; b) CETP as a protein involved in atherogenic dyslipidemia associated with the insulin resistance syndrome and c) pharmacological manipulation of the CETP by using
Keywords: evacetrapib